Cumulative Family Risk and Internet Gaming Disorder Among Adolescents: A Serial Mediating Model of Personal Growth Initiative and Gratitude - Gan, Xiong; Xiang, Guo-Xing; Li, Hao; Wang, Shao-Hua; Jin, Xin; Zhu, Cong-Shu (Frontiers in Public Health, 2022)
In the digital era, playing internet games enriches the entertainment forms for young generations. At the same time, it also raises some social issues, and internet gaming disorder (IGD) is one of them. Abundant studies demonstrate that IGD is harmful to individual physiological and psychological health. Therefore, it is necessary to figure out the reasons and mechanisms behind this phenomenon. Based on the ecological systems theory, the present study investigated the cumulative effect of family risks on adolescent IGD and the serial mediating effects of personal growth initiative and gratitude in a chain mediation model. Using random cluster sampling, a sample of 600 Chinese adolescents was recruited to finish the questionnaire. Results of regression analysis suggested that cumulative family risks could positively predict IGD among adolescents. Moreover, personal growth initiative and gratitude mediated the relationship between cumulative family risk and IGD, separately and sequentially. These findings may provide some guidance for the prevention and intervention to prevent or reduce IGD in adolescents.